2010
DOI: 10.1194/jlr.m005371
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B-containing lipoprotein assembly in microsomal triglyceride transfer protein-deficient McA-RH7777 cells

Abstract: Apolipoprotein (apo) B has a fundamental role in the transport and metabolism of plasma triacylglycerols (TAGs) and cholesterol and is synthesized primarily in hepatocytes and enterocytes ( 1-3 ). ApoB is present as a single molecule per lipoprotein particle ( 4 ) and exists in two forms, apoB100 (the full-length protein) and apoB48 (the N-terminal 48% of apoB100). The two forms derive from the same gene by a posttranscriptional modifi cation of the apoB mRNA at codon 2,153 that converts a glutamine codon to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…We demonstrated that BMSl97636 and BMS-200150, potent inhibitors of MTP activity (32), had no effect on the synthesis and secretion of apoB:1000-containing particles (11). In a subsequent study (12), we used MTP-deficient McA-RH7777 cells and demonstrated that the near complete absence of MTP had no effect on the synthesis and secretion of apoB:1000 (12). Likewise, identical levels of labeled lipids were found associated with apoB:1000-containing particles secreted by parental and MTP-deficient McA-RH7777 cells (12).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…We demonstrated that BMSl97636 and BMS-200150, potent inhibitors of MTP activity (32), had no effect on the synthesis and secretion of apoB:1000-containing particles (11). In a subsequent study (12), we used MTP-deficient McA-RH7777 cells and demonstrated that the near complete absence of MTP had no effect on the synthesis and secretion of apoB:1000 (12). Likewise, identical levels of labeled lipids were found associated with apoB:1000-containing particles secreted by parental and MTP-deficient McA-RH7777 cells (12).…”
Section: Discussionmentioning
confidence: 72%
“…Although MTP has a distinct preference for TAG and cholesteryl esters, it also has a weak PL transfer activity (30), which has been suggested to be sufficient for the initiation of apoB particle assembly in nonhepatic COS7 cells (31). To test this potential role of MTP in cells of hepatic origin, we undertook comprehensive studies that included the use of MTP inhibitors (11) and rat hepatoma McA-RH7777 cells with 98% deficiency in MTP at both the mRNA and protein levels (12). We demonstrated that BMSl97636 and BMS-200150, potent inhibitors of MTP activity (32), had no effect on the synthesis and secretion of apoB:1000-containing particles (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extrusion of the first 1000 residues (βα1 domain) and association with phospholipid within the endoplasmic reticulum (ER) lumen are necessary for the initiation of particle assembly and may not require the activity of MTP. 7 The length of the domain of B100, necessary for MTP-dependent particle assembly, is still under debate. 8,9 Multiple interactions of apoB with MTP and lipid transfer form partially lipidated particles through size-dependent linear lipidation and result in formation of low-density lipoprotein (LDL)-VLDL2 particles that act as precursors to VLDL1.…”
Section: Vldl Assembly and Hepatic Vldl Overproductionmentioning
confidence: 99%